Sosialisasi Pemanfaatan Video Edukatif pada Sikap Tanggung Jawab Siswa MTs. NWDI Juet Kabupaten Lombok Timur - Hadi Gunawan Sakti (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2023)
Learning activities using educational videos are one of the supports in efforts to manage or control themselves from the low attitude of responsibility that is often experienced by students, so they need to be fostered and directed properly. Responsibility is human awareness of intentional or unintentional behavior or actions. Responsibility also means acting as an embodiment of awareness of one's obligations. The low attitude of responsibility will have an adverse impact, such as the occurrence of a learning process that is not conducive and is unable to think positively in the social environment. This service activity aims to improve teacher understanding and skills in developing media as a tool for conveying learning material, so it is hoped that through this activity it can make the process of forming a better student personality through the use of learning media in the form of educational videos on student responsibility. The method of implementing community service includes, coordination of activities, preparation of tools and materials, implementation, and evaluation. The results of this community service activity were greeted with enthusiasm and motivation in carrying out these activities, from the practical results it can be concluded that 80% of the socialization participants were able to make good use of educational videos.